LIFESTYLE MODIFICATION AND BLOOD PRESSURE CONTROL AMONG PATIENTS WITH HYPERTENSION: A CROSS-SECTIONAL STUDY - Yusiana Vidhiastutik (PRIMA WIYATA HEALTH, 2026)
Background: Hypertension remains one of the leading non-communicable diseases worldwide and is a major contributor to cardiovascular morbidity and mortality. Despite the availability of effective pharmacological treatments, achieving optimal blood pressure control remains a significant challenge. Lifestyle modification, including healthy dietary practices, regular physical activity, weight management, smoking cessation, and stress reduction, is widely recognized as a fundamental component of hypertension management. However, the extent to which lifestyle modification influences blood pressure control among patients with hypertension remains an important area of investigation. Objectives: This study aimed to examine the relationship between lifestyle modification and blood pressure control among patients with hypertension. Methods: A cross-sectional study was conducted among 36 patients diagnosed with hypertension in the working area of Pelas Primary Health Center, Kediri Regency, East Java, Indonesia. Participants were selected using a simple random sampling technique. Data were collected using a structured questionnaire assessing lifestyle modification practices, including dietary behavior, physical activity, weight management, smoking cessation, stress management, and adherence to healthy lifestyle recommendations. Blood pressure was measured using a calibrated digital sphygmomanometer following standardized procedures. Lifestyle modification was categorized into poor, moderate, and good levels, while blood pressure status was classified as controlled or uncontrolled based on established hypertension guidelines. Data were analyzed using descriptive statistics, Chi-square tests, and multivariable logistic regression. Statistical significance was set at p < .05. Results: The findings showed that 50.0% of participants demonstrated moderate lifestyle modification, while 27.8% reported good lifestyle modification practices. More than half of the participants (58.3%) had uncontrolled blood pressure. A significant association was found between lifestyle modification and blood pressure control (χ² = 9.71, p = .008). Participants with good lifestyle modification practices exhibited a substantially higher proportion of controlled blood pressure (80.0%) compared with those with moderate (33.3%) and poor (12.5%) lifestyle modification. Logistic regression analysis revealed that good lifestyle modification was independently associated with blood pressure control (AOR = 5.84; 95% CI = 1.42–24.03; p = .014). Conclusion: Lifestyle modification was significantly associated with blood pressure control among patients with hypertension. Patients who practiced healthier lifestyle behaviors were more likely to achieve controlled blood pressure. Strengthening lifestyle-based interventions and self-management support programs may improve hypertension outcomes and reduce the risk of cardiovascular complications.